The Interaction Design Competency Framework - A tool to understand what industry wants from interaction design education - Dunford, Adam (My University, 2016)
Voices within both industry and academia contend that interaction design education falls short in preparing students for their contribution in the workforce. While some of this may indeed be due to inadequate education, industry practitioners themselves disagree with one another on what interaction design education should include, making it difficult for education to answer those needs. This master’s thesis focuses on finding and understanding what industry expects from interaction design education. Based on literature reviews, interviews with industry and academic personnel, analysis of job listings in the field, and surveys of design practitioners, common factors emerged that identify critical aspects of this understanding. These factors—including disagreements within industry and within academia, the limitations of education in covering the breadth of possible subjects, the importance of the portfolio in hiring, and the de-emphasis industry gives to formal education— make it clear that there is not just one ideal list of educational subjects that all interaction designers should possess. Instead, thinking of competencies (i.e. the skills and knowledge needed to be an interaction designer) in broader categories makes it easier to accommodate differing perspectives while still considering them as part of interaction design. The Interaction Design Competency Framework formalizes these competency categories, presenting the results in a format that provides a simple overview of what areas are the most important for interaction design. This framework structure then makes it possible to summarize the emphases of a given job, job category or degree program, as well as provide a mechanism for comparing them with one another— something that wasn’t possible before. An accompanying website, WhatsaDesigner.com, provides a survey for users to submit their own opinions on what industry needs and expects and see the results of that information in an interactive visualization of the Interaction Design Competency Framework. In this way, one can determine what industry needs and expects from not just education but from any interaction designer, who in turn can better prepare for jobs in interaction design.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction